Stabilizing Cellular Barriers: Raising the Shields Against COVID-19 - Hanchard, Julia; Capó-Vélez, Coral M.; Deusch, Kai; Lidington, Darcy; Bolz, Steffen-Sebastian (Frontiers in Endocrinology, 2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its clinical manifestation (COVID-19; coronavirus disease 2019) have caused a worldwide health crisis. Disruption of epithelial and endothelial barriers is a key clinical turning point that differentiates patients who are likely to develop severe COVID-19 outcomes: it marks a significant escalation in respiratory symptoms, loss of viral containment and a progression towards multi-organ dysfunction. These barrier mechanisms are independently compromised by known COVID-19 risk factors, including diabetes, obesity and aging: thus, a synergism between these underlying conditions and SARS-CoV-2 mechanisms may explain why these risk factors correlate with more severe outcomes. This review examines the key cellular mechanisms that SARS-CoV-2 and its underlying risk factors utilize to disrupt barrier function. As an outlook, we propose that glucagon-like peptide 1 (GLP 1) may be a therapeutic intervention that can slow COVID-19 progression and improve clinical outcome following SARS-CoV 2 infection. GLP 1 signalling activates barrier promoting processes that directly oppose the pro-inflammatory mechanisms commandeered by SARS-CoV-2 and its underlying risk factors.